Skizofrenia Paranoid - Siti Akramah; Mila Astari Harahap (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Paranoid schizophrenia is a condition of mental and behavioral disorders characterized by disturbances in thoughts, perceptions, feelings and awareness of patients who are fully conscious and intellectually can still be maintained. According to WHO, the prevalence of schizophrenia in 2021 will reach 24 million people, and the prevalence of schizophrenia experienced from 2019-2021 has increased by 54%. The 47 year old patient was taken by his family to the emergency room at Cut Meutia Hospital with complaints that the patient often had tantrums. This complaint began 13 when the family felt a change in the patient's behavior. Based on the family's information, 2 days before entering the hospital, the patient took their child away for 1 day, without being given food, the patient also carried a sharp weapon. From the patient's confession, he said he wanted to go to Saudi Arabia with his child. The patient is also restless, pacing back and forth, without a clear goal. Patients also often wander around at night and have difficulty sleeping, patients often bring home objects that do not belong to the patient when they return home after wandering around. Psychiatric status obtained a general impression of appearance according to age with medium stature, brown skin, clear consciousness, dull affect, auditory hallucinations, non-realistic thought forms, coherent thought flow, and delusional thought content, view 1 (the patient completely denies that he is sick). The diagnosis was adjusted to PPDGJ III and the patient was diagnosed as paranoid schizophrenia. Inpatients at RSCM in the UPIP room are given therapy with lodomer 5mg/ml extra, risperidone 2x2mg, diazepam 1x2mg.